A 3D body posture analysis framework during merging and lane-changing maneuvers. Issue 5 (3rd September 2018) - Kondyli, A.; Barmpoutis, A.; Sisiopiku, V. P.; Zhang, L.; Zhao, L.; Islam, M. M.; Patil, S. S.; Rostami Hosuri, S.
ABSTRACT: Although significant advances have been done with respect to vehicle technology and roadway construction, driver behavior remains the number one contributing factor of traffic crashes worldwide. Studies show that one of the major causes of crashes is driver inattention, which may occur when drivers are involved with secondary activities (e.g., texting, talking on the phone, or eating), and when they fail to follow the cues of the surrounding environment while driving. The objective of this study was to develop a method that monitors driver body posture and movements inside the cabin and test it among different drivers when performing merging and lane-changing maneuvers, because these types of maneuvers require significant body movement and may also result in unsafe situations. The developed method was applied in a naturalistic setting where 35 drivers were invited to participate. Participants' 3D body posture was recorded with the use of a low-cost infrared depth sensor (Microsoft Kinect). Participants' eye gaze was also recorded with the help of an eye-tracking equipment. This article presents analysis results of 3D body posture in conjunction with the eye-tracking information during 236 merging and 287 lane-changing maneuvers.